Rock electrical property measuring device, rock electrical property measuring method and application
The integrated rock electrical property measurement device addresses inaccuracies in existing methods by combining two-phase and four-phase electrode techniques with flexible electrodes, improving accuracy and flexibility in rock electrical property measurements.
Patent Information
- Application Number
- CN202411338726.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-25
AI Technical Summary
Existing rock electrical property measurement methods, such as the two-phase and four-phase electrode methods, suffer from issues like poor contact with the sample, electrode polarization, signal interference, and high costs, leading to inaccurate measurements.
A combined rock electrical property measurement device that integrates both two-phase and four-phase electrode methods, using flexible electrodes like Ag/AgCl and graphene-modified carbon fiber electrodes, allowing for selection based on rock conditions, and a full metal shell design to reduce interference.
The device enhances measurement accuracy and flexibility by broadening the frequency bandwidth and reducing signal interference, providing accurate measurements across various rock conditions.
Smart Images

Figure CN119246954A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of rock electrical property measurement devices, and in particular relates to a rock electrical property measurement device, a rock electrical property measurement method and an application thereof. Background Art
[0002] As a natural medium, rock has certain electrical properties. Different types of rocks have different electrical conductivity, magnetic permeability, polarization and dielectric properties. Generally speaking, the electrical conductivity of rock is very poor, but when there is a fluid with high conductivity in the rock cracks, the conductivity of the rock will increase; or when there are minerals with high conductivity in the rock, the conductivity of the rock will also increase. Therefore, the electrical properties of rock are closely related to the type of rock, structure, porosity, fluid type, etc. Studying the electrical properties of rock plays a vital role in geophysical exploration.
[0003] The parameters that characterize the electrical properties of rocks mainly include resistivity, conductivity, conductance, polarizability, and dielectric constant. At present, the main method for measuring the electrical properties of rocks is the Ohm's law method, which obtains the electrical parameters of rocks by applying voltage to the rocks and measuring the current. It is mainly divided into the two-phase electrode method and the four-phase electrode method.
[0004] The two-phase electrode method has the advantages of low cost and simple operation. At present, there are several schemes for the electrodes used in the two-phase electrode method to measure the electrical properties of rocks: one is to use copper rods as electrodes and copper sulfate cotton pads as coupling agents to form non-polarized electrodes; the second is to use lead with weak polarization ability as electrodes; the third is to use stainless steel as electrodes. The first scheme can ensure good contact between the electrode and the sample, and is very stable. The polarization phenomenon of the electrode is not obvious, but the copper sulfate solution will penetrate into the sample during measurement and change the electrical properties of the sample. Although the second and third schemes will not change the electrical properties of the sample, the contact with the sample is poor, and there is a certain polarization phenomenon, and the measurement accuracy is low. At the same time, because the power supply electrode and the measuring electrode are the same electrode during the two-phase electrode method measurement, there is a coupling interference phenomenon of the signal, and the electrode polarization phenomenon is serious during low-frequency measurement, resulting in inaccurate measurement results.
[0005] When measuring rock resistivity using the four-phase electrode method, the power supply electrode and the measuring electrode are separated, which helps to eliminate mutual interference of signals, interference of contact resistance, and polarization of measuring electrodes, and has better measurement stability and accuracy. However, the four-phase electrode method is complex to operate and has high costs. In high-frequency measurements, there is also the problem of mutual interference of measurement line signals. In addition, some potential electrodes in the four-phase electrode method need to go deep into the sample, which causes changes in sample properties and affects the accuracy of the measurement.
[0006] Therefore, it is of great significance to provide a measuring device that can accurately measure the electrical properties of rocks. Summary of the invention
[0007] The present invention aims to solve one or more technical problems existing in the above-mentioned prior art, and at least provide a beneficial choice or create conditions. Specifically, the present invention provides a rock electrical property measurement device, which has good electrical property measurement accuracy.
[0008] The inventive concept of the present invention: the rock electrical property measuring device of the present invention includes a T-shaped fixing rod, the T-shaped fixing rod includes a horizontal rod and a vertical rod perpendicular to the horizontal rod; a sliding rod, the sliding rod includes a first sliding rod, a second sliding rod and a third sliding rod; the second sliding rod is located on the left side of the vertical rod, the first sliding rod and the third sliding rod are located on the right side of the vertical rod in sequence, and the sliding rod slides along the horizontal rod; a first electrolytic cell, a second electrolytic cell, the first electrolytic cell is arranged between the second sliding rod and the vertical rod, and the second electrolytic cell is arranged between the first sliding rod and the third sliding rod; a first flexible electrode, a second flexible electrode, the lower ends of the first sliding rod and the vertical rod are respectively connected with the first flexible electrode and the second flexible electrode which are arranged relatively. The rock electrical property measuring device of the present invention is designed in an integrated manner, that is, the two-phase electrode method for measuring rock electrical properties and the four-phase electrode method for measuring rock electrical properties are combined in the same device. When measuring rock samples, the four-phase electrode method can be selected for low-frequency measurement, and the two-phase electrode method can be selected for high-frequency measurement. When measuring wide-band, a measurement scheme combining the two-phase electrode method and the four-phase electrode method is selected, which greatly broadens the frequency bandwidth of rock electrical property measurement and improves measurement accuracy.
[0009] Therefore, a first aspect of the present invention provides a rock electrical property measurement device.
[0010] Specifically, the rock electrical property measuring device comprises a T-shaped fixing rod, and the T-shaped fixing rod comprises a horizontal rod and a vertical rod perpendicular to the horizontal rod;
[0011] Sliding rods, the sliding rods comprising a first sliding rod, a second sliding rod and a third sliding rod; the second sliding rod is located on the left side of the vertical rod, the first sliding rod and the third sliding rod are located on the right side of the vertical rod in sequence, and the sliding rods slide along the horizontal rod;
[0012] A first electrolytic cell and a second electrolytic cell, wherein the first electrolytic cell is disposed between the second sliding rod and the vertical rod, and the second electrolytic cell is disposed between the first sliding rod and the third sliding rod;
[0013] A first flexible electrode and a second flexible electrode; the lower ends of the first sliding rod and the vertical rod are respectively connected with the first flexible electrode and the second flexible electrode which are arranged opposite to each other.
[0014] Preferably, the T-shaped fixing rod is a metal rod.
[0015] Preferably, the sliding rod and the vertical rod are both hollow metal rods, a through hole is provided at the upper end of the sliding rod, and the sliding rod is connected to the horizontal rod through the through hole.
[0016] Specifically, the sliding rod is connected to the horizontal rod of the T-shaped fixing rod through the through hole, so that the sliding rod can slide horizontally along the horizontal rod.
[0017] Preferably, the upper end of the sliding rod is fixedly connected to the horizontal rod via a fixing bolt.
[0018] Specifically, when the sliding rod needs to be fixed, the fixing bolt is tightened, and when the sliding rod needs to slide left and right along the horizontal rod, the fixing bolt is loosened.
[0019] Preferably, the upper ends of the first sliding rod and the vertical rod are respectively provided with a first terminal and a second terminal, the first terminal is connected to the first flexible electrode through a wire in the first sliding rod; the second terminal is connected to the second flexible electrode through a wire in the vertical rod.
[0020] Preferably, an electrode gasket is provided between the first flexible electrode and the first sliding rod, and between the second flexible electrode and the vertical rod, respectively.
[0021] Preferably, a connecting column is provided at a position inside the lower end of the first sliding rod corresponding to the electrode gasket, and the electrode gasket is connected to the first terminal through the connecting column and a wire; a connecting column is provided at a position inside the lower end of the vertical rod corresponding to the electrode gasket, and the electrode gasket is connected to the second terminal through the connecting column and a wire.
[0022] Preferably, the upper ends of the second sliding rod and the third sliding rod are respectively provided with a third terminal and a fourth terminal, the third terminal is connected to the first electrolytic cell via a wire in the second sliding rod; the fourth terminal is connected to the second electrolytic cell via a wire in the third sliding rod.
[0023] Preferably, the first connecting terminal, the second connecting terminal, the third connecting terminal and the fourth connecting terminal are respectively located on the upper end surfaces of the first sliding rod, the vertical rod, the second sliding rod and the third sliding rod.
[0024] Preferably, the first electrolytic cell and the second electrolytic cell both comprise a steel cell and a rubber layer located on the inner and outer surfaces of the steel cell; the inner and outer sides of the side walls of the first electrolytic cell and the second electrolytic cell are connected by a metal gasket.
[0025] Preferably, the metal gasket is I-shaped.
[0026] Preferably, electrode gaskets are provided between the vertical rod and the first electrolytic cell side wall, between the second sliding rod and the first electrolytic cell side wall, between the first sliding rod and the second electrolytic cell side wall, and between the third sliding rod and the second electrolytic cell side wall.
[0027] Preferably, the side walls of the first electrolytic cell are respectively connected to the wires in the second sliding rod and the wires in the vertical rod through the electrode gaskets; the side walls of the second electrolytic cell are respectively connected to the wires in the first sliding rod and the wires in the third sliding rod through the electrode gaskets.
[0028] Preferably, a connecting column is provided at a position inside the lower end of the second sliding rod corresponding to the electrode gasket, and the electrode gasket is connected to the third terminal in sequence through the connecting column and the wire in the second sliding rod; a connecting column is provided at a position inside the lower end of the vertical rod corresponding to the electrode gasket, and the second flexible electrode is connected to the second terminal in sequence through the electrode gasket, the connecting column and the wire in the vertical rod.
[0029] Preferably, a connecting column is provided at a position inside the lower end of the first sliding rod corresponding to the electrode gasket, and the first flexible electrode is connected to the first terminal in sequence through the electrode gasket, the connecting column, and the wire in the first sliding rod; a connecting column is provided at a position inside the lower end of the third sliding rod corresponding to the electrode gasket, and the electrode gasket is connected to the fourth terminal in sequence through the connecting column and the wire in the third sliding rod.
[0030] Preferably, the first flexible electrode and the second flexible electrode are both patch electrodes.
[0031] Preferably, the first flexible electrode and the second flexible electrode are independently selected from any one of an Ag / AgCl flexible electrode and a graphene-modified carbon fiber flexible electrode.
[0032] The present invention can select Ag / AgCl flexible electrodes or graphene-modified carbon fiber flexible electrodes as electrodes for measuring rock electrical properties according to the actual conditions of rock samples, thereby making the rock electrical property measurement more accurate.
[0033] Preferably, the Ag / AgCl flexible electrode comprises a base layer, a flexible conductive layer, a silver conductive film layer and an Ag / AgCl electrode layer stacked in sequence; the flexible conductive layer comprises a polydimethylsiloxane matrix and silver powder.
[0034] Preferably, the base layer is a silver sheet, and the surface of the silver sheet has convex points; the convex points make the mechanical coupling between the base layer of the electrode and the flexible conductive layer tighter.
[0035] Preferably, the flexible conductive layer comprises a polydimethylsiloxane matrix and internally doped nano silver powder.
[0036] Specifically, for the flexible conductive layer, polydimethylsiloxane (PDMS) has the following advantages: first, it has a low Young's modulus and has good flexibility and stretchability; second, it has strong corrosion resistance, good transparency and stability in a wide range of operating temperatures, and can be used as a substrate material for large-area transparent flexible electronic devices or thermal stability devices; third, it is easy to combine with electronic materials to fix the electrode material on its surface, and PDMS can be prepared into a structure with a certain geometric shape as needed to improve its ductility and meet the requirements of the coplanar structure; fourth, the preparation process is simple and easy to operate. In addition, after doping nano-silver powder inside PDMS, PDMS has both good flexibility and conductivity.
[0037] Preferably, the silver conductive film layer is silver foil.
[0038] Preferably, the Ag / AgCl electrode layer has a porous structure, and the Ag / AgCl electrode layer is composed of Ag particles and AgCl particles.
[0039] Preferably, the Ag / AgCl electrode in the Ag / AgCl electrode layer is a non-polarizable electrode.
[0040] Specifically, the porous structure enables the Ag / AgCl electrode layer to have a larger specific surface area, greatly increasing the contact area between the electrode and the rock sample; and the non-polarizable characteristics of the Ag / AgCl electrode can greatly reduce the measurement error caused by electrode polarization during the measurement process, thereby improving the accuracy of the test.
[0041] Preferably, the method for preparing the Ag / AgCl flexible electrode comprises the following steps:
[0042] (1) Preparation of nano-Ag / AgCl suspension;
[0043] (2) immersing the silver foil in the nano-Ag / AgCl suspension obtained in step (1), drying to obtain an electrode embryo, and then sintering to form a porous Ag / AgCl electrode on the silver foil, that is, obtaining a silver conductive film with an Ag / AgCl electrode layer attached thereto;
[0044] (3) Placing the electrode substrate at the bottom of the mold, adding PDMS liquid prepolymer into the mold, and then placing the silver conductive film with the Ag / AgCl electrode layer attached on the surface of the PDMS liquid prepolymer, curing, and demolding to obtain the Ag / AgCl flexible electrode.
[0045] Preferably, in step (1), the preparation process of the nano-Ag / AgCl suspension is:
[0046] S1: Adding AgNO3 into polyvinylpyrrolidone (PVP) solution to obtain PVP-AgNO3 solution;
[0047] S2: adding saturated sodium chloride solution to the PVP-AgNO3 solution to obtain a PVP-AgCl dispersion;
[0048] S3: Adding nano silver powder to the PVP-AgCl dispersion system to obtain a PVP-Ag / AgCl dispersion system to obtain the nano Ag / AgCl suspension.
[0049] Preferably, in step (2), after drying, the obtained product is repeatedly immersed in a nano-Ag / AgCl suspension until a uniform and dense PVP-Ag / AgCl is attached to the surface of the silver foil, thereby obtaining an electrode embryo.
[0050] Preferably, in step (2), after forming a porous Ag / AgCl electrode on the silver foil, the silver foil is cleaned and dried to obtain a silver conductive film with an Ag / AgCl electrode layer attached thereto.
[0051] Preferably, in step (3), silver powder, PDMS and a curing agent are mixed to obtain a PDMS liquid prepolymer.
[0052] Preferably, the mass ratio of the silver powder, PDMS and curing agent is (4-6): (8-12): 1; further preferably, the mass ratio of the silver powder, PDMS and curing agent is (4.5-5.5): (9-11): 1; further preferably, the mass ratio of the silver powder, PDMS and curing agent is 5:10:1.
[0053] Preferably, in step (3), the curing temperature is 50-70°C, and the curing time is 0.8-1.2h; further preferably, in step (3), the curing temperature is 55-65°C, and the curing time is 0.9-1.1h; further preferably, in step (3), the curing temperature is 60°C, and the curing time is 1h.
[0054] Preferably, in step (3), the preparation method of the electrode substrate is: using a punching machine with convex points to press convex points on the surface of the silver sheet to obtain the electrode substrate.
[0055] Specifically, the protrusions are closely arranged.
[0056] Specifically, the present invention adopts the infiltration and pulling method to make the Ag / AgCl flexible electrode as the rock electrical property measurement electrode. When preparing the flexible conductive layer, the PDMS material is used as the flexible substrate, and nano silver powder is doped therein as the conductive channel, while retaining the flexible characteristics of PDMS, the conductivity of the substrate is enhanced; when preparing the Ag / AgCl electrode layer, the sol-gel method of the PVP system is adopted, and PVP is used as a dispersant to prevent AgCl from agglomerating, so that the AgCl particle size generated by the reaction is small and evenly dispersed; PVP is used as an adhesive to make the nano Ag powder and AgCl mix evenly; PVP is used as a pore-forming agent to make the sintered Ag / AgCl electrode layer have tiny and dense pores, which can increase the specific surface area of the electrode layer. The infiltration and pulling method is used to make the Ag / AgCl electrode layer adhere to the silver conductive film, so that the electrode layer is thick and dense, which can improve the service life of the electrode. And the material of the Ag / AgCl electrode layer is selected from Ag and AgCl, and a non-polarized electrode is formed during measurement, which greatly reduces the measurement error caused by electrode polarization and improves the measurement accuracy.
[0057] Preferably, the graphene-modified carbon fiber flexible electrode comprises a base layer, a flexible conductive layer, a carbon fiber conductive film and a graphene-modified carbon fiber electrode layer stacked in sequence; the flexible conductive layer comprises a polydimethylsiloxane matrix and silver powder.
[0058] Preferably, the base layer, the flexible conductive layer and the corresponding preparation methods are the same as the base layer and the flexible conductive layer in the Ag / AgCl flexible electrode.
[0059] Preferably, the flexible conductive layer comprises a polydimethylsiloxane matrix and internally doped nano silver powder.
[0060] Preferably, the preparation process of the graphene-modified carbon fiber flexible electrode comprises the following steps:
[0061] (1) immersing the carbon fiber sheet in an acetone solution, ultrasonically cleaning, drying, and polishing the surface to obtain a carbon fiber conductive film;
[0062] (2) using the carbon fiber conductive film obtained in step (1) as the positive electrode and the stainless steel plate as the negative electrode, and then placing the whole in a graphene oxide dispersion, electrophoretically depositing to obtain a graphene oxide modified carbon fiber electrode layer, and then reducing in a nitrogen environment to obtain a graphene modified carbon fiber electrode layer;
[0063] (3) Placing the electrode substrate at the bottom of the mold, adding PDMS liquid prepolymer into the mold, and then placing the graphene-modified carbon fiber conductive film on the surface of the PDMS liquid prepolymer, curing, and demolding to obtain a graphene-modified carbon fiber flexible electrode.
[0064] Preferably, the method for preparing the carbon fiber conductive film comprises the following steps: immersing the carbon fiber sheet in an acetone solution, ultrasonically cleaning to obtain a desizing carbon fiber sheet, and then drying and polishing the surface of the carbon fiber sheet to make it rough to obtain a carbon fiber conductive film.
[0065] Preferably, in step (2), the electrophoretic deposition is performed under ultrasound.
[0066] Preferably, in step (2), the graphene oxide modified carbon fiber conductive film is first stabilized under an air pump and then reduced in a nitrogen environment.
[0067] Preferably, the stable temperature is 240-330°C, and the stable time is 1.5-2.5h; further preferably, the stable temperature is 260-300°C, and the stable time is 1.8-2.2h; further preferably, the stable temperature is 280°C, and the stable time is 2h.
[0068] Preferably, the reduction temperature is 600-800°C, and the reduction time is 4-6 min; further preferably, the reduction temperature is 650-750°C, and the reduction time is 4.5-5.5 min; further preferably, the reduction temperature is 700°C, and the reduction time is 5 min.
[0069] Preferably, in step (3), the electrode substrate, PDMS liquid prepolymer and preparation method are the same as those of the Ag / AgCl flexible electrode.
[0070] Specifically, carbon fiber has the characteristics of light weight, corrosion resistance, and high strength. As an electrode material, carbon fiber has a weak background current and rich surface activity, strong adaptability, a wide detection range, and can be made into different types of fiber fabrics according to different needs, which greatly broadens the scope of use of carbon fiber as an electrode. The surface of the carbon fiber electrode prepared by the electrochemical modification method is attached with graphene. The deposition of graphene on the surface of the carbon fiber can increase the specific surface area and surface roughness of the carbon fiber, so that the interface bonding area between the carbon fiber and the test sample can be more effectively increased, and the coupling resistance between the flexible electrode and the substrate (test sample) can be reduced. In addition, graphene can increase the active functional groups and chemical activity on the surface of the carbon fiber, so that the carbon fiber and the substrate are connected in a chemically bonded manner, and the mechanical interlocking force between the electrode and the sample to be tested is enhanced. In summary, the use of chemically modified carbon fiber electrodes as rock electrical property measurement electrodes retains the advantages of carbon fiber's good mechanical strength, strong heat resistance and corrosion resistance, as well as weak background current and rich surface activity as an electrode material. By modifying the carbon fiber with graphene, it also makes up for the shortcomings of carbon fiber's own poor conductivity and poor anti-interference ability, making the electrical property measurement of the rock more accurate.
[0071] Specifically, the present invention can select corresponding electrodes according to the actual conditions of the rock samples. For rock samples with small porosity, graphene-modified carbon fiber flexible electrodes can be selected, which can increase the contact area and reduce the contact resistance. For rock samples with large porosity or high surface roughness, Ag / AgCl flexible electrodes can be selected, which can reduce the polarization degree or contact resistance of the electrode and ensure the accuracy of the measurement.
[0072] A second aspect of the present invention provides a method for measuring rock electrical properties.
[0073] Specifically, the rock electrical property measurement method uses the rock electrical property measurement device described in the first aspect of the present invention to perform two-phase electrode measurement method measurement and / or four-phase electrode measurement method measurement;
[0074] The two-phase electrode measurement method comprises the following steps:
[0075] The two end surfaces of the rock sample are respectively attached to the first flexible electrode and the second flexible electrode, and then the second terminal is connected to the voltage end of the measuring instrument, and the first terminal is connected to the current end of the measuring instrument to perform measurement;
[0076] The four-phase electrode measurement method comprises the following steps:
[0077] The two end faces of the rock sample are respectively fitted with the first flexible electrode and the second flexible electrode, and then the third terminal and the fourth terminal are connected to the voltage end of the measuring instrument, and the first terminal and the second terminal are connected to the current end of the measuring instrument for measurement.
[0078] Preferably, when installing the rock sample, loosen the fixing bolts, and fit the two end faces of the rock sample with the first flexible electrode and the second flexible electrode respectively. After they are completely fit, tighten the fixing bolts so that the first flexible electrode and the second flexible electrode clamp the rock sample.
[0079] Specifically, the two-phase electrode measurement method and the four-phase electrode measurement method respectively measure the contact resistance, resistivity, electrode polarization and impedance spectrum of the rock sample, and when the two-phase electrode measurement method is used to measure the impedance spectrum of the rock sample, the frequency range is 1Hz-10MHz, and when the four-phase electrode measurement method is used to measure the impedance spectrum of the rock sample, the frequency range is 1MHz-10kHz.
[0080] Preferably, when the two-phase electrode measurement method and the four-phase electrode measurement method need to be combined, the two-phase electrode measurement method is performed first, and then the four-phase electrode measurement method is performed.
[0081] Preferably, the measuring instrument includes any one of a multimeter and an impedance analyzer.
[0082] Preferably, for larger-scale rocks in the field, an array electrode measurement scheme and multi-point measurement can be adopted.
[0083] The third aspect of the present invention provides an application of the rock electrical property measurement device described in the first aspect of the present invention in the field of rock measurement.
[0084] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0085] (1) The rock electrical property measurement device of the present invention adopts an integrated design, that is, the two-phase electrode method for measuring rock electrical properties and the four-phase electrode method for measuring rock electrical properties are combined in the same device. When measuring rock samples, the four-phase electrode method can be selected for low-frequency measurement, and the two-phase electrode method can be selected for high-frequency measurement. When measuring wide-band, a measurement scheme combining the two-phase electrode method and the four-phase electrode method is selected, which greatly broadens the frequency bandwidth of rock electrical property measurement and improves measurement accuracy.
[0086] (2) The measuring device of the present invention adopts a full metal shell design. During measurement, the metal shell, measuring electrodes and measuring instrument are grounded together to reduce signal interference and improve measurement accuracy.
[0087] (3) The present invention can select Ag / AgCl flexible electrodes or graphene-modified carbon fiber flexible electrodes as electrodes for measuring rock electrical properties according to the actual conditions of the rock samples, making the rock electrical property measurements more accurate and flexible. In addition, when the present invention adopts the quadrupole method for measurement, metal gaskets of different materials can be selected according to different electrolytes. For example, when the electrolyte solution is CuSO4, a copper gasket can be selected; when the electrolyte solution is KCl or NaCl, a silver gasket can be selected. That is, the present invention can provide different measuring electrodes and measurement schemes, which can be selected according to actual measurement conditions and measurement requirements, so that the measuring device has higher applicability.
[0088] (4) The present invention adopts the design of flexible patch electrodes. In the field environment or in an environment where there are no conditions for preparing rock samples, the flexible electrodes can still be attached to the surface of the rock sample to complete the measurement. For large-scale rocks in the field, an array electrode measurement scheme can be adopted. Multi-point measurement can fully understand the real-time electrical characteristics of the rock. Through subsequent data processing, internal imaging of the rock can be achieved, and the global characteristics of the rock's electrical properties can be grasped. BRIEF DESCRIPTION OF THE DRAWINGS
[0089] Figure 1 This is a schematic diagram of a rock electrical property measurement device according to Embodiment 1 of the present invention;
[0090] Figure 2 Schematic diagram of the structure of the Ag / AgCl flexible electrode in Example 1 of the present invention;
[0091] Figure 3 This is a schematic diagram of the structure of the first electrolytic cell and the second electrolytic cell in Example 1 of the present invention;
[0092] Figure 4 This is a schematic diagram of a rock electrical property measurement device when measuring using a two-phase electrode method in Example 1 of the present invention;
[0093] Figure 5 Schematic diagram of a rock electrical property measurement device when measuring using the four-phase electrode method in Example 1 of the present invention;
[0094] Figure 6 This is a schematic diagram of the structure of a graphene-modified carbon fiber flexible electrode in Example 2 of the present invention;
[0095] Figure 7 The contact resistance results of rock samples with different water contents measured by the rock electrical property measurement device of Example 1 and Comparative Example 1 of the present invention are shown in FIG.
[0096] Figure 8 This is a graph showing the error results of the actual resistivity and measured resistivity of rock samples with different water contents measured by the rock electrical property measurement device in Example 1 of the present invention and Comparative Example 1;
[0097] Fig. 9 This is a diagram showing the results of the rock electrical property measurement device of Example 1 of the present invention measuring a rock sample using the two-phase electrode method and the four-phase electrode method;
[0098] Fig.10 Schematic diagram of array electrode measurement.
[0099] Among them, 1 is a T-shaped fixing rod, 2 is a first sliding rod, 3 is a second sliding rod, 4 is a third sliding rod, 5 is a fixing bolt, 6 is a spring, 7 is a first terminal, 8 is a second terminal, 9 is a third terminal, 10 is a fourth terminal, 11 is an electrode gasket, 12 is a wire, 13 is a connecting column, 14 is an Ag / AgCl flexible electrode, 15 is a first electrolytic cell, 16 is a second electrolytic cell, 17 is an electrode substrate, 18 is a flexible conductive layer, 19 is a silver conductive film, 20 is a porous Ag / AgCl electrode layer, 21 is nano-Ag particles, 22 is AgCl particles, 23 is a steel tank, 24 is a rubber shell, 25 is a metal gasket, 26 is a rock sample, 27 is an electrode substrate, 28 is a flexible conductive layer, 29 is a carbon fiber conductive film, and 30 is a graphene-modified carbon fiber electrode layer. DETAILED DESCRIPTION
[0100] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0101] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0102] Schematic diagram of a rock electrical property measurement device according to embodiment 1 of the present invention is shown in FIG. Figure 1 As shown; the structural schematic diagram of the Ag / AgCl flexible electrode is shown Figure 2 As shown, Figure 2 Figure (a) is a schematic diagram of the structure of the Ag / AgCl flexible electrode. Figure 2 Figure (b) is an enlarged view of the Ag / AgCl electrode layer in Figure (a); the structural schematic diagram of the first electrolytic cell and the second electrolytic cell is as follows Figure 3 shown.
[0103] Example 1
[0104] like Figure 1 , 2 As shown in FIG. 3 , a rock electrical property measuring device comprises a T-shaped fixing rod 1 for fixing, a first sliding rod 2, a second sliding rod 3, and a third sliding rod 4 for clamping,
[0105] The T-shaped fixed rod 1 (stainless steel) includes a horizontal rod and a vertical rod perpendicular to the horizontal rod, and the first sliding rod 2, the second sliding rod 3, and the third sliding rod 4 are all hollow metal rods (stainless steel); the second sliding rod 3 is located on the left side of the vertical rod, and the first sliding rod 2 and the third sliding rod 4 are located on the right side of the vertical rod in sequence; the upper ends of the first sliding rod 2, the second sliding rod 3, and the third sliding rod 4 are all provided with through holes, and the first sliding rod 2, the second sliding rod 3, and the third sliding rod 4 are sleeved on the horizontal rod through the through holes and can slide horizontally along the horizontal rod, and the first sliding rod 2, the second sliding rod 3, the third sliding rod 4 and the horizontal rod are respectively fixed with fixing bolts 5;
[0106] Springs 6 are respectively provided between the first sliding rod 2 and the vertical rod, between the second sliding rod 3 and the vertical rod, and between the third sliding rod 4 and the first sliding rod 2;
[0107] The upper end surfaces of the first sliding rod 2, the second sliding rod 3, the third sliding rod 4, and the vertical rod are respectively installed with the first wiring terminal 7, the third wiring terminal 9, the fourth wiring terminal 10, and the second wiring terminal 8; the inner and outer side surfaces of the lower ends of the first sliding rod 2 and the vertical rod, and the inner side surfaces of the lower ends of the second sliding rod 3 and the third sliding rod 4 are all provided with electrode pads 11; the first sliding rod 2, the second sliding rod 3, the third sliding rod 4, and the vertical rod are all provided with wires 12 inside, and the positions inside the lower ends corresponding to the electrode pads 11 are respectively provided with connecting posts 13; the electrode pads 11 are respectively connected to the first wiring terminal 7, the second wiring terminal 8, the third wiring terminal 9, and the fourth wiring terminal 10 through the corresponding connecting posts 13 and the wires 12;
[0108] Ag / AgCl flexible electrodes 14 are respectively provided on the electrode gaskets 11 of the first sliding rod 2 and the vertical rod, and the two Ag / AgCl flexible electrodes are arranged opposite to each other; the Ag / AgCl flexible electrode 14 on the first sliding rod 2 is connected to the first wiring terminal 7 through the electrode gasket 11, the connecting column 13, and the wire 12 in sequence; the Ag / AgCl flexible electrode 14 on the vertical rod is connected to the second wiring terminal 8 through the electrode gasket 11, the connecting column 13, and the wire 12 in sequence;
[0109] The Ag / AgCl flexible electrodes 14 on the first sliding rod 2 and the vertical rod fit the two ends of the rock sample, and by adjusting the position of the first sliding rod 2 left and right, the two Ag / AgCl flexible electrodes 14 clamp the rock sample;
[0110] A first electrolytic cell 15 is provided between the second sliding rod 3 and the vertical rod, and a second electrolytic cell 16 is provided between the first sliding rod 2 and the third sliding rod 4;
[0111] The Ag / AgCl flexible electrode 14 includes an electrode substrate 17, a flexible conductive layer 18, a silver conductive film 19, and a porous Ag / AgCl electrode layer 20 which are arranged in sequence; the electrode substrate 17 is a silver sheet with densely distributed bumps on the surface, the flexible conductive layer 18 is polydimethylsiloxane doped with nano silver powder, the silver conductive film 19 is a silver foil, and the Ag / AgCl electrode layer 20 is composed of nano Ag particles 21 and AgCl particles 22;
[0112] The first electrolytic cell 15 and the second electrolytic cell 16 are both made of steel, and the base is a steel cell 23. The inner and outer sides of the steel cell 23 are wrapped with a rubber shell 24. The inner and outer sides of the side walls of the first electrolytic cell 15 and the second electrolytic cell 16 are connected by an I-shaped metal gasket 25.
[0113] The method for preparing the Ag / AgCl flexible electrode 14 comprises the following steps:
[0114] (1) Preparation of Nano-Ag / AgCl Suspension:
[0115] S1: Dissolve 10 g of polyvinyl pyrrolidone (PVP) in 100 mL of 75% ethanol solution, and continue stirring until the PVP is completely dissolved. The molecular weight of PVP is 1,300,000, to obtain a mixed solution.
[0116] S2: Add 20 g of silver nitrate (AgNO3) to the mixed solution of step S1, and continue stirring until the silver nitrate is completely dissolved to obtain a PVP-AgNO3 solution, which is slightly brown;
[0117] S3: At room temperature, weigh 8 g (excess) sodium chloride and dissolve it in 19 g water, and continue stirring until the sodium chloride is completely dissolved to obtain a saturated sodium chloride solution;
[0118] S4: slowly drop the saturated sodium chloride solution obtained in step S3 into the ultrasonically stirred PVP-AgNO3 solution, and continue ultrasonic stirring for 4 hours after the dropwise addition is completed, so that the sodium chloride and silver nitrate react completely to generate silver chloride, and obtain a PVP-AgCl dispersion system, which is milky white at this time;
[0119] S5: Under ultrasonic stirring, 15 g of nano silver powder (5 nm) was slowly added to the PVP-AgCl dispersion to obtain a PVP-Ag / AgCl dispersion, and the mixture was continuously stirred until the silver powder was evenly dispersed to obtain a nano Ag / AgCl suspension, which was now dark gray.
[0120] (2) Preparation of electrode embryos by infiltration and pulling method:
[0121] S6: Cut the 0.1 mm thick silver foil into a 5 cm diameter disc;
[0122] S7: Under ultrasonic conditions, the silver foil was completely immersed in the nano-Ag / AgCl suspension, taken out after 5 seconds, and placed in a hot air oven at 60°C for drying for 30 minutes;
[0123] S8: immersing the dried silver foil again in the nano-Ag / AgCl suspension, and repeating step S7 for 10 times, until the surface of the silver foil is covered with evenly and densely dry PVP-Ag / AgCl to obtain an electrode embryo;
[0124] (3) Preparation of a silver conductive film with an Ag / AgCl electrode layer attached:
[0125] S9: placing the electrode embryo in a muffle furnace, heating it to 400°C at a heating rate of 1.5°C / min, sintering it for 120min, burning off the PVP, making the Ag / AgCl on the surface of the silver foil porous, and obtaining a porous electrode;
[0126] S10: placing the porous electrode in 20% by mass dilute hydrochloric acid for 180 minutes to remove the excess NaCl in step S3 and the impurities introduced during the manufacturing process to obtain an acid-washed electrode; placing the acid-washed electrode in clean water for 10 minutes to obtain a cleaned electrode; placing the cleaned electrode in a hot air oven at 60° C. for 30 minutes to dry to obtain a silver conductive film with an Ag / AgCl electrode layer attached;
[0127] (4) Preparation of flexible conductive layer and Ag / AgCl flexible electrode:
[0128] S11: Weigh 20 g of PDMS main agent (PDMS) into a beaker, add 10 g of silver powder with a particle size of 50 nm, and stir magnetically for 24 h to fully disperse the silver powder in the PDMS main agent to obtain a dispersion system; add 2 g of PDMS curing agent (platinum catalyst) to the dispersion system, stir for 1 hour to completely mix the curing agent and the main agent to obtain a PDMS liquid prepolymer;
[0129] S12: Cut a 1 mm thick silver plate into silver sheets with a diameter of 5 cm, and use a punch with convex points to press dense convex points on the surface of the silver sheet to obtain an electrode substrate; place the electrode substrate at the bottom of the mold, and then pour the PDMS liquid prepolymer into the mold, and place the mold in a vacuum drying oven for 1 hour to eliminate bubbles in the PDMS liquid condensate; then place a silver conductive film with an Ag / AgCl electrode layer attached to the surface of the PDMS liquid prepolymer, and place the entire mold in a drying oven at 60°C for 1 hour to solidify the electrode, and demold after complete solidification to obtain an Ag / AgCl flexible electrode.
[0130] The rock electrical properties measuring device of Example 1 is used below to measure the rock electrical properties. Taking marble with a relatively smooth surface as an example, preparatory work is first performed. Before the test, the marble rock sample is cut into cylindrical samples with a diameter of 5 cm, soaked in water for 24 hours, and then the surface moisture is wiped dry and covered with waterproof tape on the side to prevent the evaporation of moisture from causing changes in the rock parameters during measurement; after the rock sample is prepared, the Ag / AgCl flexible electrode 14 is taken out of the NaCl solution and installed relatively on the electrode gasket 11 at the lower end of the vertical rod and the first sliding rod 2 respectively.
[0131] For the two-phase electrode method measurement, loosen the fixing bolt 5 on the first sliding rod 2, slide the first sliding rod 2 away from the T-shaped fixing rod 1, and make the bottom surface of the rock sample 26 completely fit with the flexible electrode 14 on the vertical rod, and then tighten the fixing bolt 5 so that the flexible electrode 14 at the lower end of the vertical rod and the flexible electrode 14 at the lower end of the first sliding rod 2 completely clamp the rock sample 26; then connect the terminal 7 to the current end of the measuring instrument (digital multimeter), and connect the terminal 8 to the voltage end of the measuring instrument (digital multimeter), and measure the contact resistance, resistivity, electrode polarization rate and impedance spectrum of the rock sample 26 respectively. When using this method to measure the impedance spectrum, the frequency range is 1Hz-10MHz.
[0132] For the four-phase electrode method measurement, according to the electrolyte saturated potassium chloride solution, a suitable metal gasket 25 is selected as a copper sheet and installed on the first electrolytic cell 15 and the second electrolytic cell 16. On the basis of the diode method measurement, loosen the fixing bolt 5 at the upper end of the second sliding rod 3, and slide the second sliding rod 3 to move away from the vertical rod of the T-shaped fixing rod 1, install the first electrolytic cell 15 between the second sliding rod 3 and the lower end of the vertical rod, and make the electrode gasket 11 at the lower end of the second sliding rod 3 and the vertical rod completely fit with the metal gasket 25 of the first electrolytic cell, and then tighten the fixing bolt 5 at the upper end of the second sliding rod 3; the second electrolytic cell 16 The installation is the same as the first electrolytic cell 15; after the first electrolytic cell 15 and the second electrolytic cell 16 are installed, the electrolyte (saturated potassium chloride solution) is poured into the first electrolytic cell 15 and the second electrolytic cell 16 respectively, so that the electrolyte completely covers the metal gasket 25; then the wires of the measuring instrument are connected to the terminals respectively, wherein the third terminal 9 and the fourth terminal 10 are connected to the voltage terminal of the measuring instrument (digital multimeter), and the first terminal 7 and the second terminal 8 are connected to the current terminal of the measuring instrument (digital multimeter), and then the contact resistance, resistivity and impedance spectrum of the rock sample 26 are measured respectively. When the impedance spectrum is measured using this method, the frequency range is 1MHz-10kHz.
[0133] The schematic diagrams of the measuring devices for the two-phase electrode method and the four-phase electrode method are as follows: Figure 4 , 5 shown.
[0134] For the four-phase electrode method measurement, after the measurement is completed, it is necessary to remove the first electrolyte tank 15 and the second electrolytic tank 16, and pour the electrolyte therein into the waste liquid pool, wash with clean water and wipe dry, unscrew the metal gasket 25 on the side wall, wash and dry; and remove the Ag / AgCl flexible electrode 14 and place it in a NaCl solution to ensure electrode activation.
[0135] Example 2
[0136] The only difference between Example 2 and Example 1 is that Example 2 uses a graphene-modified carbon fiber flexible electrode to replace the Ag / AgCl flexible electrode 14 of Example 1, and the rock of Example 2 is red sandstone. The rest is the same as Example 1.
[0137] The graphene-modified carbon fiber flexible electrode in Example 2 includes an electrode substrate 27, a flexible conductive layer 28, a carbon fiber conductive film 29, and a graphene-modified carbon fiber electrode layer 30 arranged in sequence; the electrode substrate 27 and the flexible conductive layer 28 are the same as the electrode substrate and the flexible conductive layer in the Ag / AgCl flexible electrode in Example 1.
[0138] The structural schematic diagram of the graphene-modified carbon fiber flexible electrode in Example 2 of the present invention is as follows Figure 6 shown.
[0139] The method for preparing a graphene-modified carbon fiber flexible electrode comprises the following steps:
[0140] (1) Preparation of carbon fiber conductive film: a carbon fiber sheet with a thickness of 0.1 mm was cut into a disc with a diameter of 5 cm, and the disc-shaped carbon fiber sheet was immersed in an acetone solution for ultrasonic cleaning for 1 h to obtain a desizing carbon fiber sheet; the carbon fiber sheet was rinsed with deionized water and dried in an oven at 85° C.; then the surface of the carbon fiber sheet was polished to make it rough, thereby obtaining a carbon fiber conductive film;
[0141] (2) Preparation of graphene oxide:
[0142] S1: Assemble a 250mL reaction bottle in an ice water bath, add 115mL concentrated nitric acid and stir to obtain reactant A (concentrated nitric acid); add 5g graphite powder, 2.5g sodium nitrate and 15g potassium permanganate to reactant A and continue stirring, control the reaction temperature below 20°C, raise the temperature to 35°C after the reaction is complete, and continue stirring for 30min; then add an appropriate amount of deionized water, continue stirring for 20min, and then add hydrogen peroxide until the solution turns bright yellow, filter the reactant to obtain precipitate B and filtrate C;
[0143] S2: adding an excess of barium chloride solution to the filtrate C until no new precipitate is generated in the filtrate C; washing the precipitate B with a dilute nitric acid solution, washing the precipitate B with deionized water, and then drying to obtain graphene oxide;
[0144] (3) Preparation of graphene oxide dispersion: 50 mg of graphene oxide was dispersed in 500 mL of isopropanol and ultrasonically treated at room temperature for 1 h to obtain a graphene oxide dispersion;
[0145] (4) Electrophoretic deposition of graphene oxide: The carbon fiber conductive film is used as the positive electrode and the stainless steel plate is used as the negative electrode, and then placed in a graphene oxide dispersion liquid. A voltage of 17 V is applied and graphene oxide is electrophoretically deposited under ultrasound to obtain a graphene oxide-modified carbon fiber electrode layer.
[0146] (5) Reducing graphene oxide: The graphene oxide modified carbon fiber electrode layer is kept at 280° C. for 2 h under an air pump to stabilize the material, and the stabilized material is reduced at 700° C. for 5 min under a nitrogen pump to reduce the graphene oxide to graphene, thereby obtaining a graphene modified carbon fiber electrode layer;
[0147] (6) Preparation of flexible conductive layer and graphene-modified carbon fiber flexible electrode: A graphene-modified carbon fiber flexible electrode is obtained by using the same method as step (4) in the preparation process of Ag / AgCl flexible electrode.
[0148] Comparative Example 1
[0149] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 uses a Cu electrode to replace the Ag / AgCl flexible electrode 14 of Example 1, and the rest is the same as Example 1.
[0150] Measurement results
[0151] A digital multimeter was used to connect the connection terminals 7, 8, 9, and 10 of the rock electrical property measurement device of Example 1 and Comparative Example 1 to measure the impedance of rock samples with different water contents (0.83%, 1.01%, 2%, 2.94%, and 4.36%). The measurements were performed 100 times in succession, and the arithmetic mean of the measurement data was used as the measurement result.
[0152] In the measurement, the contact resistance is included in the result, so it is necessary to measure the contact resistance between the rock sample and the electrode to correct the measured resistance. The rock cores with the same dry density are made into rock samples with the same cross-sectional area and lengths of 2, 4, 6, 8, and 10 cm. At this time, the resistance of the rock sample is proportional to the length of the rock sample:
[0153] R = k·L (1);
[0154] In formula (1), R is the resistance of the rock sample, L is the length of the rock sample, and k is the proportional coefficient. Due to the introduction of contact resistance, the measured resistance of the rock sample is linearly related to the length:
[0155] R m =k·L+R c (2);
[0156] In formula (2), R m and R c They represent the measured resistance and contact resistance respectively. According to formula (2), a linear equation between the measured resistance and the length of the rock sample is fitted, and its intercept is the contact resistance.
[0157] The standard resistivity expression for rock samples is:
[0158]
[0159] In formula (3), ρ 18 is the resistivity of the sample at 18°C, S is the cross-sectional area of the rock sample along the current direction, and α is an experimental constant, usually 0.025°C -1 , T represents the experimental temperature, and the measured resistance R m With contact resistance R c The difference between the two represents the corrected resistance, while the resistivity before contact resistance correction is:
[0160]
[0161] In formula (4), ρ m Indicates the resistivity before contact resistance correction.
[0162] The resistivity error is used to express the error before and after resistivity correction:
[0163]
[0164] In formula (5), E ρ represents the resistivity error.
[0165] Example 1, Comparative Example 1 The contact resistance results of rock samples with different water contents measured by the measuring device are as follows: Figure 7 As shown, Figure 7 Figure (a) is a schematic diagram of contact resistance measurement and calculation. Figure 7 Figure (b) is a contact resistance diagram of a rock sample with a water content of 0.83% (w=0.83%) measured by the measuring device of Example 1 and Comparative Example 1. Figure 7 Figure (c) is a contact resistance diagram of a rock sample with a water content of 1.01% (w=1.01%) measured by the measuring devices of Example 1 and Comparative Example 1. Figure 7 Figure (d) is a contact resistance diagram of a rock sample with a water content of 2% (w=2%) measured by the measuring devices of Example 1 and Comparative Example 1. Figure 7 Figure (e) is a contact resistance diagram of a rock sample with a water content of 2.94% (w=2.94%) measured by the measuring devices of Example 1 and Comparative Example 1. Figure 7 Figure (f) is a contact resistance diagram of a rock sample with a water content of 4.36% (w=4.36%) measured by the measuring devices of Example 1 and Comparative Example 1. The horizontal axis Length represents the length of the rock sample, the vertical axis Resistance represents the contact resistance, cm and Ω represent the units of centimeters and ohms respectively; k Cu Indicates the proportionality coefficient when measuring copper electrodes, k Ag / AgCl Indicates the proportionality coefficient when measuring Ag / AgCl electrode.
[0166] Depend on Figure 7It can be seen that the core resistivity decreases with the increase of water content, which is consistent with the theory. The fitting lines of the two electrodes do not pass through the origin, indicating that there is contact resistance in the measurement. When the water content is 0.83% and 1.01%, the contact resistance of the Cu electrode is about 3kΩ, and the contact resistance of the Ag / AgCl electrode is 652.6Ω and 650Ω respectively; when the water content is 2.00%, 2.94% and 4.36%, the contact resistance of the copper electrode is greater than 500Ω, and the contact resistance of the Ag / AgCl electrode is less than 100Ω. When the water content of the rock sample is 4.36%, the contact resistance is only 32.42Ω. The results show that for the same rock sample, the contact resistance when measured with the Ag / AgCl electrode is at least 74% lower than the contact resistance when measured with the Cu electrode.
[0167] Substitute the measured resistance of the core samples with different water contents and a length of 2 cm into formula (4) to obtain the resistivity before correction. Substitute the measured resistance and contact resistance into formula (3) to obtain the standard resistivity. Use formula (5) to calculate the resistivity error. The error between the actual resistivity and the measured resistivity of the core samples with a length of 2 cm and different water contents is as follows: Figure 8 As shown. Among them, the horizontal axis Moisture content represents the moisture content, Resistivity (kΩ·m) represents the resistivity, CorrectedResistivity represents the corrected resistivity, Ag / AgCl represents the error result of Example 1, Cu represents the error result of Comparative Example 1, the actual resistivity is the standard resistivity, and the measured resistivity is the resistivity before correction.
[0168] Figure 8 Comparing the resistivity calculation results before and after the correction of the contact resistance, the resistivity errors of the copper electrode in comparative example 1 are almost all above 30%, while the resistivity errors of the Ag / AgCl electrode in embodiment 1 are all less than 10%. When the water content of the rock sample is 2.94%, the resistivity error is as low as 2.44%. In general, the accuracy of the Ag / AgCl flexible electrode in embodiment 1 in measuring rock resistivity is at least 25% higher than that of the Cu electrode.
[0169] The electrical properties of the rock samples were measured by the two-phase electrode method and the four-phase electrode method using the measuring device of Example 1. The measurement results are as follows: Fig. 9 As shown. Fig. 9 It can be seen that compared with the rock impedance data calculated theoretically, within the lower frequency band, the rock impedance data measured by the four-phase electrode method has high accuracy, while the rock impedance data measured by the two-phase electrode method has low accuracy; within the higher frequency band, the rock impedance data measured by the two-phase electrode method has high accuracy, while the rock impedance data measured by the four-phase electrode method has low accuracy; only by combining the two can accurate rock impedance test data be obtained.
[0170] In addition, when measuring rock electrical properties, array electrode measurement can be used according to the shape of the rock, that is, multiple flexible electrodes are attached to the surface of the rock, and the flexible electrodes are connected to the measuring instruments to conduct all-round monitoring of rock electrical properties and electrical imaging inside the rock. Fig.10 shown.
[0171] In summary, the rock electrical property measurement device of the present invention adopts an integrated design, that is, the two-phase electrode method for measuring rock electrical properties and the four-phase electrode method for measuring rock electrical properties are combined in the same device. When measuring rock samples, the four-phase electrode method can be selected for low-frequency measurement, and the two-phase electrode method can be selected for high-frequency measurement. When measuring wide-band, the two-phase electrode method and the four-phase electrode method are combined to form a measurement scheme, which greatly broadens the frequency bandwidth of rock electrical property measurement and improves measurement accuracy. At the same time, by adopting a specific Ag / AgCl flexible electrode or a graphene-modified carbon fiber flexible electrode, the electrical property measurement of the rock is made more accurate. In addition, the present invention can select an Ag / AgCl flexible electrode or a graphene-modified carbon fiber flexible electrode according to the actual situation of the rock sample. When using the quadrupole method for measurement, metal gaskets of different materials can be selected according to different electrolytes, that is, the measuring device of the present invention has higher applicability.
[0172] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A rock electrical property measuring device, characterized in that: It comprises a T-shaped fixing rod, wherein the T-shaped fixing rod comprises a horizontal rod and a vertical rod perpendicular to the horizontal rod; Sliding rods, the sliding rods comprising a first sliding rod, a second sliding rod and a third sliding rod; the second sliding rod is located on the left side of the vertical rod, the first sliding rod and the third sliding rod are located on the right side of the vertical rod in sequence, and the sliding rods slide along the horizontal rod; A first electrolytic cell and a second electrolytic cell, wherein the first electrolytic cell is disposed between the second sliding rod and the vertical rod, and the second electrolytic cell is disposed between the first sliding rod and the third sliding rod; A first flexible electrode and a second flexible electrode; the lower ends of the first sliding rod and the vertical rod are respectively connected with the first flexible electrode and the second flexible electrode which are arranged opposite to each other.
2. The rock electrical property measuring device according to claim 1, characterized in that: The sliding rod and the vertical rod are both hollow metal rods; a through hole is provided at the upper end of the sliding rod, and the sliding rod is connected to the horizontal rod through the through hole.
3. The rock electrical property measuring device according to claim 1, characterized in that: The upper ends of the first sliding rod and the vertical rod are respectively provided with a first terminal and a second terminal. The first terminal is connected to the first flexible electrode via a wire in the first sliding rod; the second terminal is connected to the second flexible electrode via a wire in the vertical rod.
4. The rock electrical property measuring device according to claim 1, characterized in that: The upper ends of the second sliding rod and the third sliding rod are respectively provided with a third terminal and a fourth terminal. The third terminal is connected to the first electrolytic cell via a wire in the second sliding rod; the fourth terminal is connected to the second electrolytic cell via a wire in the third sliding rod.
5. The rock electrical property measuring device according to claim 1, characterized in that: The first flexible electrode and the second flexible electrode are independently selected from any one of an Ag / AgCl flexible electrode and a graphene-modified carbon fiber flexible electrode.
6. The rock electrical property measuring device according to claim 5, characterized in that: The Ag / AgCl flexible electrode comprises a base layer, a flexible conductive layer, a silver conductive film layer and an Ag / AgCl electrode layer which are stacked in sequence; the flexible conductive layer comprises a polydimethylsiloxane matrix and silver powder.
7. The rock electrical property measuring device according to claim 6, characterized in that: The Ag / AgCl electrode layer has a porous structure, and the Ag / AgCl electrode layer comprises Ag particles and AgCl particles.
8. The rock electrical property measuring device according to claim 5, characterized in that: The graphene-modified carbon fiber flexible electrode comprises a base layer, a flexible conductive layer, a carbon fiber conductive film and a graphene-modified carbon fiber electrode layer stacked in sequence; the flexible conductive layer comprises a polydimethylsiloxane matrix and silver powder.
9. A rock electrical property measurement method, characterized in that: The rock electrical property measuring device according to any one of claims 1 to 8 is used to perform two-phase electrode measurement method and / or four-phase electrode measurement method; The two-phase electrode measurement method comprises the following steps: The two end surfaces of the rock sample are respectively attached to the first flexible electrode and the second flexible electrode, and then the second terminal is connected to the voltage end of the measuring instrument, and the first terminal is connected to the current end of the measuring instrument to perform measurement; The four-phase electrode measurement method comprises the following steps: The two end faces of the rock sample are respectively fitted with the first flexible electrode and the second flexible electrode, and then the third terminal and the fourth terminal are connected to the voltage end of the measuring instrument, and the first terminal and the second terminal are connected to the current end of the measuring instrument for measurement.
10. Application of the rock electrical property measurement device according to any one of claims 1 to 8 in the field of rock measurement.
Citation Information
Patent Citations
Annular arrangement type multi-needle biological tissue dielectric spectrum characteristic measuring probe and method
CN102445574A
Measuring apparatus for measuring electric property of rock-ore and method thereof
CN102520256A
Electrical isolation unit for measuring rock resistivity
CN102809695A
Flexible physiological dry electrode and preparation method thereof
CN102824168A
Device for measuring electrical property of rock / ore specimen
CN102944799A
